The impact of local decentralization on economic growth: evidence from U.S. counties - George W. Hammond; Mehmet Serkan Tosun (Institute for the Study of Labor (IZA), 2009)
We analyze the impact of fiscal decentralization on U.S. county population, employment, and real income growth. Our findings suggest that government organization matters for local economic growth, but that the impacts vary by government unit and by economic indicator. We find that single-purpose governments per square mile have a positive impact on metropolitan population and employment growth, but no significant impact on nonmetropolitan counties. In contrast, the fragmentation of general-purpose governments per capita has a negative impact on employment and population growth in nonmetropolitan counties. Our results suggest that local government decentralization matters differently for metropolitan and nonmetropolitan counties.
Keywords: E62; H7; R11; 330; Fiscal decentralization; metropolitan; nonmetropolitan; population; employment; income; spatial econometrics; Fiskalische Dezentralisierung; Dezentralisierung; Regionale Entwicklung; Regionales Wachstum; Ballungsraum; Ländlicher Raum; USA